Investigation of effects of transferrin-conjugated gold nanoparticles on hippocampal neuronal activity and anxiety behavior in mice - GARİP, GÜNSELİ AYŞE (My University, 2023)
Gold nanoparticles (GNPs) have been widely used in medicine such as imaging, drug delivery and therapeutics due to their multifunctional properties. Alterations in neuronal function may contribute to various neurological diseases. Transferrin plays a primary role in iron transportation and delivery and has recently been utilized for drug delivery to the brain. We have investigated effects of transferrin-conjugated GNPs (Tf-GNPs) on anxiety and locomotor behavior in vivo and also hippocampal neuronal activity ex vivo. Electrophysiological effects of Tf-GNP on hippocampal neurons were determined by patch clamp method. Fifteen male young adult C57BL/6 mice were randomly divided into three groups as control (200 µL PBS), GNP (bare GNP; 2.2 μg/g in PBS) and Tf-GNPs (2.2 μg/g Tf-GNP). Animals intraperitoneally received the respective treatments for seven consecutive days and were subjected to elevated plus maze (EPM) and open field tests (OFT). Ex vivo, firing frequency of the neurons significantly increased by GNP treatment (p < 0.001). In vivo, animals in Tf-GNP group showed significantly longer distance in open arms but significantly lower number of entries to the open arms in EPM (p < 0.05). Mice received bare GNPs had significantly higher locomotor activity in OFT (p < 0.05), while Tf-GNP did not alter the locomotor activity significantly (p = 0.051). Animals in Tf-GNP group spent significantly longer time in the peripheral zone in OFT (p < 0.05). The present findings have shown that Tf-GNP induces anxiety-like behavior without altering spontaneous firing rate of hippocampal neurons. We suggest that neurobiological effects of Tf-GNP should be pre-determined before using in medical applications.
Keywords: Tıp; Histoloji-Embriyoloji; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Tıp Bilimleri; Temel Bilimler; Medicine; Histology and Embryology; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Fundamental Medical Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); HÜCRE BİYOLOJİSİ; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Life Sciences (LIFE); MOLECULAR BIOLOGY & GENETICS; CELL BIOLOGY; BIOCHEMISTRY & MOLECULAR BIOLOGY; Moleküler Biyoloji; Klinik Biyokimya; Hücre Biyolojisi; Molecular Biology; Clinical Biochemistry; Cell Biology; Action potential; Anxiety-like behaviors; Electrophysiology; Gold nanoparticles; Locomotor activity; Transferrin; OXIDE NANOPARTICLES; BIODISTRIBUTION; NEUROTOXICITY; DISORDERS; DELIVERY; INVOLVEMENT; CHANNELS; ANTIBODY; THERAPY; STRESS